Sistem Pendukung Keputusan untuk Menilai Kesejahteraan Wilayah DIY dengan Metode SMART - Muhammad Salman Al Farisy; Sri Winiarti (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2025)
Welfare in the Special Region of Yogyakarta (DIY) is disrupted by urbanization and development inequality, which leads to poverty and other social problems. This research uses the Waterfall method which includes requirements analysis, design, implementation, and testing. Data were collected through interviews, and literature studies. The results of the study show that: first, the system developed is able to provide welfare ratings with high accuracy. Second, system validation through MAE calculation produces a value of 0.285, indicating a minimum error rate, so that the system can provide reliable predictions and support data-driven decision-making. Usability evaluation using the System Usability Scale (SUS) obtained a score of 73.9 which is in the good category and shows that the system is easy to use, and the functionality test with the Black Box method shows a 100% success rate. In conclusion, SPK based on the SMART method is effective in supporting social policies.